CaMKII-dependent ryanodine receptor phosphorylation mediates sepsis-induced cardiomyocyte apoptosis - Sepúlveda, Marisa Noemí (2020)
Sepsis is associated with cardiac dysfunction, which is at least in part due to cardiomyocyte apoptosis. However, the underlying mechanisms are far from being understood. Using the colon ascendens stent peritonitis mouse model of sepsis (CASP), we examined the subcellular mechanisms that mediate sepsis-induced apoptosis. Wildtype (WT) CASP mice hearts showed an increase in apoptosis respect to WT-Sham. CASP transgenic mice expressing a CaMKII inhibitory peptide (AC3-I) were protected against sepsis-induced apoptosis. Dantrolene, used to reduce ryanodine receptor (RyR) diastolic sarcoplasmic reticulum (SR) Ca2+ release, prevented apoptosis in WTCASP. To examine whether CaMKII-dependent RyR2 phosphorylation mediates diastolic Ca2+ release and apoptosis in sepsis, we evaluated apoptosis in mutant mice hearts that have the CaMKII phosphorylation site of RyR2 (Serine 2814) mutated to Alanine (S2814A). S2814A CASP mice did not show increased apoptosis. Consistent with RyR2 phosphorylation-dependent enhancement in diastolic SR Ca2+ release leading to mitochondrial Ca2+ overload, mitochondrial Ca2+ retention capacity was reduced in mitochondria isolated from WT-CASP compared to Sham and this reduction was absent in mitochondria from CASP S2814A or dantrolene-treated mice. We conclude that in sepsis, CaMKII-dependent RyR2 phosphorylation results in diastolic Ca2+ release from SR which leads to mitochondrial Ca2+ overload and apoptosis.